PENGELOLAAN DIGITAL PR DALAM MENGEMAS KONTEN DAKWAH DI INSTAGRAM @MASJIDTRANS - Wulan Mulya Asih; Khoiruddin Muchtar; Yusuf Zaenal Abidin (Jurnal Riset Komunikasi (JURKOM), 2020)
Digital PR is a public relations function in the digital era, one of its tasks is to manage social media owned by agencies. Trans Studio Bandung Mosque is one of the mosques that has successfully implemented digital PR management in packaging the social media account Instagram @masjidtrans in an effort to attract public enthusiasm. The research method used in this research is descriptive analysis method with a qualitative approach and constructivism paradigm. The results of his research are digital PR TSB Mosque successfully implemented four stages in the concept of four steps of PR namely, (1) Fact finding is done by analyzing the situation, analyzing the target audience and analyzing the media. (2). Planning: planning the goals to be achieved and making tactical planning. (3). Taking action and communication: dividing the type of content according to Instagram features, following up the content of the study to the organizer community, crosschecking content, creating accidental content, making posting strategies on Instagram and performing posting intensity and content packaging. (4). Evaluation: determine assessment indicators and make monthly reports. Digital PR management in packaging da'wah content on the Instagram account of the Trans Studio Bandung Mosque also increases the congregation who attend the presentation or event held at TSB Mosque